Intelligent Management of Energy Storage Systems in Buildings - Teixeira, Diogo Gonçalo Rolo (2017)
The usage of electricity, nowadays, suffers from large fluctuations and is inefficient, creating load management issues and a considerable carbon footprint. Within this subject, buildings are one of the main culprits, due to the high percentage of time that people spend within them. In addition, elec-tricity plays a determinant role for the comfort within buildings, creating an intrinsic need for it. Therefore, due to the occupant’s behavioural patterns, inefficiencies occur between electricity’s supply and demand. Consequently, to reach ambitious energy efficiency goals, the building sector must undergo through technological innovation enabling a better energy management. Energy management is nowadays a subject of great importance and complexity, by choosing amongst a set of sources and loads that could minimize the losses and costs. Energy management sys-tems, coupled with energy storage systems, can optimize the electricity usage, making it more efficient. Accordingly, the goal of this dissertation is to present a system able to, intelligently, manage energy storage systems, user consumptions within buildings and power sources through strictly defined strategies. This system bases itself on a decision system that, while maintaining the security, stability and quality of service of the power network, can enhance how buildings consume electricity, optimizing it and lowering the load management problems. To conclude, this dissertation aims to develop computer software, a simulator, in order to test this system’s viability and if the results globally optimize the electricity usage.